Sentencing Ashley Smith: How Prison Conditions Relate to the Aims of Punishment. Issue 2 (20th September 2017) - Kerr, Lisa
Abstract: Ashley Smith's experience in the adult prison system flowed from certain of its systemic features. This article considers whether and how it is possible to reconcile the basic commitments of sentencing law, including the legal aims of punishment, with that systemic portrait. The youth court that ordered Smith's transfer to adult custody relied upon an idealized conception of adult imprisonment, just as ordinary adult sentencing courts do. Judges purport to stipulate the severity of punishment, but tend not to consider how prison conditions will shape the severity of the sanction. Even where a particular defendant is likely to face unique difficulties in custody, courts tend to take notice in limited and rare ways. Smith's experience in adult custody challenges us to more clearly identify, and to consider extending, doctrinal sentencing rules that represent a judicial concern with the effects and prospects of imprisonment in particular cases. Résumé: L'expérience vécue par Ashley Smith dans le système carcéral pour adultes témoigne de certaines caractéristiques de ce système. Le présent article tente d'établir, d'une part, s'il est possible d'harmoniser les engagements de base des lois régissant la détermination de la peine, y compris les visées légales des sanctions, au système carcéral et, d'autre part, comment arriver à une telle harmonisation entre ces lois et la réalité de ce système. Le tribunal de la jeunesse qui a ordonné le transfert d'Ashley Smith dans un établissement correctionnel pour adultes a eu recours à une conception idéalisée de la détention des adultes, une conception partagée par les tribunaux pour adultes. Les juges prétendent stipuler la sévérité de la peine sans toutefois tenir compte du fait que les conditions de détention accroissent la sévérité de la sanction. Même si un accusé est susceptible d'éprouver des difficultés particulières durant sa détention, les tribunaux ont peu tendance à le remarquer ou à en tenir compte. L'expérience de détention d'Ashley Smith dans un établissement correctionnel pour adultes lance le défi d'identifier plus précisément, voire d'élargir, la doctrine en matière de détermination de la peine témoignant d'une préoccupation judiciaire pour les effets de la détention dans certains cas particuliers.